Student Experience and Wellbeing: Relationship-Rich Education, Well-Being, and Inclusive Environments - Felten, Peter (Rastros Rostros, 2026)
Universities worldwide are facing a decisive inflection point that demands strategic, systemic action to transform student experience and well-being. While student-centered education has long been supported by research on learning and critical pedagogy, its urgency has intensified due to demographic change, technological disruption, and profound social and economic pressures. These forces have redefined who accesses higher education, how learning occurs, and what students expect from universities. In the context of post-pandemic challenges and the rapid expansion of generative AI, institutions must reaffirm their role as human-centered environments that cultivate belonging, meaning, and resilience. This paper argues that the future of higher education depends on embedding student experience and well-being into the core of institutional strategy and practice. Central to this transformation is the concept of relationship-rich education, understood as learning environments sustained by meaningful interactions among students, faculty, and staff. Evidence shows that strong academic and social relationships enhance cognitive development, mental health, persistence, and overall flourishing, benefiting not only students but also educators and institutional culture. However, structural constraints — including institutional scale, technology misuse, and misaligned incentives — frequently erode these essential connections. To address these challenges, the report proposes eight strategic priorities: designing relationship-rich learning ecosystems; integrating active and collaborative pedagogies into curricula; empowering students as co-creators of academic and institutional life; adopting a holistic approach to well-being that includes students, faculty, and staff; fostering inclusive and equity-driven environments; guiding the use of AI and technology through human-centered principles; reimagining professional development as relational growth; and embedding belonging and purpose into institutional culture. Together, these strategies outline a shift toward a relational, human-centered model of institutional excellence. By aligning mission, policy, and everyday practice around student experience and well-being, universities can strengthen learning outcomes, promote equity, and contribute more effectively to the public good.